RANCANG BANGUN DAN PROTEKSI INVERTER PURE SINE WAVE SPWM 500 WATT BERBASIS MIKROKONTROLER MENGGUNAKAN FUZZY LOGIC - Wafiq Safaroz (Jurnal Informatika dan Teknik Elektro Terapan, 2023)
The application of power electronics is growing in the DC to AC converter system often called (Inverter). The inverter system utilizes a DC voltage source generated by a battery, power supply, or other DC voltage source, which will later be converted to AC voltage by the inverter. The development of microcontrollers as a driver for generating PWM signals on inverters encourages us to continue to develop. One of the developments of the microcontroller is ESP32. This study aims to produce a single-phase inverter with a pure sine wave output using the ESP32 driver as the SPWM signal generator. Besides that, to maximize the performance of the inverter, it is necessary to add a protection system to reduce the risk of damage to the inverter or the load. The use of fuzzy method is used to stabilize the voltage.